Algebraische Zahlentheorie: 12.8. bis 18.8.1973 - Hasse, Helmut; Roquette, Peter (Tagungsbericht, 1973)
J. V. Armitage, Nottingham; E. Becker, Köln; F. Bertrandias, Grenoble; D. Brizolis, Pomona; H. Brückner, Hamburg; P. Bundschuh, Köln; J. W. S. Cassels, Cambridge; M. Eichler, Basel; G. Frei-Imfeld, Quebec; A. Fröhlich, London; W.-D. Geyer, Erlangen; B. Gordon, Los Angeles; F. Halter-Koch, Köln; G. Harder, Bonn; H. Hasse, Hamburg; M. Hazewinkel, Rotterdam; M. Ikeda, Ankara; M. Jarden; Heidelberg; W. Jehne, Köln; K. Kiyek, Paderborn; N. Klingen, Köln; M. Knebusch, Saarbrücken; K. Lakkis, Thessaloniki; E. Lamprecht, Saarbrücken; H. Lang, Köln; B. Leicht, Heidelberg; A. Leutbecher, München; J. J. Liang, Tampa; L. R. McCulloh, Urbana; M. L. Madan, Columbus; J. Martinet, Bordeaux; C. Meyer, Köln; J. Neukirch, Regensburg; J. Ochoa, Madrid; M. Peters, Münster; A. Pfister, Mainz; M. Pohst, Köln; H. Popp, Mannheim; P. Roquette, Heidelberg; W. Scharlau, Münster; R. Schertz, Köln; A. Schinzel, Warschau; J. Sonn, Haifa; H. J. Stender, Köln; N. M. Stephens, Oxford; St. V. Ullom, Urbana; R. W. v. d. Waall, Nijmegen; H. G. Zimmer, Karlsruhe